2010
DOI: 10.1038/cdd.2010.154
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α respecifies human mesenchymal stem cells to a neural fate and promotes migration toward experimental glioma

Abstract: Bone marrow-derived human mesenchymal stem cells (hMSCs) have become valuable candidates for cell-based therapeutical applications including neuroregenerative and anti-tumor strategies. Yet, the molecular mechanisms that control hMSC transdifferentiation to neural cells and hMSC tropism toward glioma remain unclear. Here, we demonstrate that hMSCs incubated with 50 ng/ml tumor necrosis factor alpha (TNF-a) acquired astroglial cell morphology without affecting proliferation, which was increased at 5 ng/ml. TNF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 39 publications
0
58
0
1
Order By: Relevance
“…Conversely, it has been shown that fetal and adult MSCs are killed by different pathways; in particular, fetal MSCs are preferably killed via TNF a while the adult MSCs are more sensitive to FasL pathway [57]. More intriguingly, a recent study has revealed that TNF a by its own can specify human MSCs to a neural fate [58]. Based on these findings, while the final biological significance of these TNF family members in the complex apoptosis mechanism of MSCs is still elusive, we speculate that the enhanced survival in De-MSCs might be related to the downregulation of TNF receptor 1 and Fas pathway, which requires further investigation in future.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it has been shown that fetal and adult MSCs are killed by different pathways; in particular, fetal MSCs are preferably killed via TNF a while the adult MSCs are more sensitive to FasL pathway [57]. More intriguingly, a recent study has revealed that TNF a by its own can specify human MSCs to a neural fate [58]. Based on these findings, while the final biological significance of these TNF family members in the complex apoptosis mechanism of MSCs is still elusive, we speculate that the enhanced survival in De-MSCs might be related to the downregulation of TNF receptor 1 and Fas pathway, which requires further investigation in future.…”
Section: Discussionmentioning
confidence: 99%
“…The subcellular localization of β-catenin protein in the hMSCs was examined by immunocytochemistry as previously described (8). Culture slides were incubated with mouse anti-β-catenin antibodies (Santa Cruz Biotechnology) at a dilution of 1:500 in a solution containing 0.5% Triton X-100 and 10% normal goat serum (NGS) for 2 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were positive for CD105, CD166, CD29, and CD44 and negative for CD14, CD34, and CD45. hMSCs were cultured as described previously, using the mesenchymal stemcell growth medium (MSCGM) BulletKit (Lonza) (8). For experiments under serum-free conditions, hMSCs were washed with serum-free medium and incubated in DMEM supplemented with 1% Nutridoma SP (Roche Applied Science) in the presence or absence of 20 nM human recombinant TIMP-1 (Peprotech), the null-inhibition mutant Val-Val-TIMP-1, or its active analog WT TIMP-1, both kindly provided by P. Nelson, Ludwig-Maximilians-University.…”
Section: Methodsmentioning
confidence: 99%
“…As for human endothelial cells, TNF-α has a biphasic effect on CXCR4 expression, with early inhibition and late induction [138]. Furthermore, TNF-α augments expression of CXCR4 on bone marrow-derived hMSCs, which elevates SDF-1α-induced migration of hMSCs to intracranial gliomas [139]. But Han et al [140] reported that CXCR4 expression is reduced by exposure to TNF-α in primary mouse astrocytes.…”
Section: Molecular Signals Associated With the Sdf-1α/cxcr4 Axis In Gmentioning
confidence: 99%